2021
DOI: 10.1055/a-1665-9014
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Aldol Reaction of Alkenyl Esters with α-Keto Esters Catalyzed by Chiral Tin Alkoxides

Abstract: A catalytic enantioselective aldol reaction of alkenyl esters with α-ketoesters was achieved using an (R)-BINOL-derived chiral tin dibromide possessing a 4-t-butylphenyl group at 3- and 3’-positions as the chiral precatalyst in the presence of sodium methoxide and methanol. Optically active aldol products possessing a chiral tertiary carbon with up to 92% ee were diastereoselectively obtained in moderate to high yields not only from cyclic alkenyl esters but also from acyclic ones under the influence of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…6 (S)-3,3'-Bis(4''-tert-butylphenyl)-2,2'-(2,2-bisbromo-2-stannapropane-1,3-diyl)-1,1'binaphthyl (S)-4a. 7 A mixture of (S)-3,3'-bis(4''-tert-butylphenyl)-2,2'-bis(bromomethyl)-1,1'-binaphthyl [(S)-10, 1.65 g, 2.34 mmol], Sn powder (2.78 g, 23.4 mmol) and H2O (1 drop) in toluene (7 mL) was heated and refluxed for 12 h. Then whole mixture was filtrated to remove remained Sn powder. The filtrate was evaporated and concentrated in vacuo to give (S)-3,3'-bis (4…”
Section: (S)-33'-bis(trifluoromethanesulfonyloxy)-22'-dimethyl-11'-bi...mentioning
confidence: 99%
See 1 more Smart Citation
“…6 (S)-3,3'-Bis(4''-tert-butylphenyl)-2,2'-(2,2-bisbromo-2-stannapropane-1,3-diyl)-1,1'binaphthyl (S)-4a. 7 A mixture of (S)-3,3'-bis(4''-tert-butylphenyl)-2,2'-bis(bromomethyl)-1,1'-binaphthyl [(S)-10, 1.65 g, 2.34 mmol], Sn powder (2.78 g, 23.4 mmol) and H2O (1 drop) in toluene (7 mL) was heated and refluxed for 12 h. Then whole mixture was filtrated to remove remained Sn powder. The filtrate was evaporated and concentrated in vacuo to give (S)-3,3'-bis (4…”
Section: (S)-33'-bis(trifluoromethanesulfonyloxy)-22'-dimethyl-11'-bi...mentioning
confidence: 99%
“…We have previously reported that an asymmetric aldol reaction of alkenyl esters and -keto esters occurs readily in the presence of a catalytic amount of a chiral tin methoxide. 7 The alkenyl esters are smoothly transformed into chiral tin enolates in situ, and the chiral tin methoxide is regenerated from the aldol adducts under the influence of methanol. This reaction furnishes the corresponding nonracemic -hydroxy ketones having a chiral tertiary carbon in remarkable enantiomeric excesses.…”
mentioning
confidence: 99%